Increased D-dimer is associated with disease progression and increased mortality in Turkish COVID-19 patients - MERCANCI, ZEYNEP; ILGIN, CAN; OLGUN YILDIZELİ, ŞEHNAZ; KOCAKAYA, DERYA; BALCAN, MEHMET BARAN; KARAKURT, SAİT; ERYÜKSEL, SEMİHA EMEL (My University, 2023)
Objective: Coagulopathy is thought to play an important role in the development of severe COVID-19. High D-dimer levels have been reported in Chinese cohort studies. However, ethnicity has significant implications for thrombotic risk. Our aim in this study is to determine the effect of D-dimer measurements on disease prognosis and mortality in Turkish patients with COVID-19. Patients and Methods: The study was designed retrospectively. Patients over the age of 18 who were admitted to our hospital were included in the study. Results: The study included 226 patients. According to the World Health Organization staging, 75(33.2%) patients, according to the staging of Siddiqi et al., 67 (29.7%) patients progressed. In the ROC analysis performed to predict mortality, AUC value for D-dimer was found to be 82.25% (95%CI 74.8%-89.71%). When the cut-off value for D-dimer was accepted as ≥3.25mg/L, specificity was 94.15%, correctly classified rate 88.5%, positive likelihood ratio as (LR):5.69, negative LR:0.71. Conclusion: As a result, similar to the Chinese cohorts, elevated D-dimer measurements increase disease progression and mortality in Turkish patients with COVID-19. D-dimer levels of 3.25 mg/L and above, strongly determine the risk of increased mortality in the Turkish Caucasian ethnic group.
Keywords: Tıp; Sağlık Bilimleri; Temel Tıp Bilimleri; Medicine; Health Sciences; Fundamental Medical Sciences; Klinik Tıp (MED); Klinik Tıp; TIP, GENEL & DAHİLİ; Clinical Medicine (MED); CLINICAL MEDICINE; MEDICINE, GENERAL & INTERNAL; Genel Tıp; General Medicine; COVID-19; D-dimer; Ethnicity; Mortality; COVID-19; D-dimer; Mortality; Ethnicity